Response to an expert opinion on the article "Association between cardiovascular mortality and deprivation in the adult population of Russia" - A. A. Zelenina; S. A. Shalnova; S. A. Maksimov (Кардиоваскулярная терапия и профилактика, 2024)
Response to an expert opinion on the article "Association between cardiovascular mortality and deprivation in the adult population of Russia", published in the Cardiovascular Therapy and Prevention 2024;23(3):3903, contains comments and explanations for a better understanding of issues raised in expert opinion.